(3UahI GdePgH ef fgGjI GdeWdHs - (3CHh SYO YHO Gddg Hf eMeO Gdjefi Hf CHi YUQhfs ((3YeQ Hf CHj ZGfe Hf GdehUdi s)
(3ChdgG (B:s
(3jHJOC HcJGH GdUjGe s
(3BNQgG (B:s
(3jfJgi HHGH GdQgf ZjQ eVehf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1080s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(880((3C(B)) s
Keywords: (3GdJhMjO hGdedd hGdfMds